2020
DOI: 10.5194/hess-2020-101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying flood-water impacts on a lake water budget via volume-dependent transient stable isotope mass balance

Abstract: Abstract. Interactions between groundwater and surface water are often overlooked in lake water budgets, even though groundwater can significantly contribute to the total annual water inputs to a lake. Isotope mass balance models have seen significant developments in the last decade for assessing the spatial and temporal variability of hydrological processes in lakes but are generally applied assuming steady-state. While this assumption is generally acceptable for long-term water balances of large lakes, it ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…"Total flood-water inputs summed at 4.82x10 6 m 3 , which is nearly equal to the lake initial volume (i.e., 4.70x10 6 m 3 ). Similar results were obtained by C8 Falcone (2007) who studied the hydrological processes influencing the water balance of lakes in the Peace-Athabasca Delta, Alberta (Canada) using water isotope tracers. They reported that the springtime freshet (in 2003) did replenish the flooded lakes from 68% to > 100% (88% in average)".…”
Section: Importance Of Flood-water Inputs In the Water Balance Partitionsupporting
confidence: 82%
“…"Total flood-water inputs summed at 4.82x10 6 m 3 , which is nearly equal to the lake initial volume (i.e., 4.70x10 6 m 3 ). Similar results were obtained by C8 Falcone (2007) who studied the hydrological processes influencing the water balance of lakes in the Peace-Athabasca Delta, Alberta (Canada) using water isotope tracers. They reported that the springtime freshet (in 2003) did replenish the flooded lakes from 68% to > 100% (88% in average)".…”
Section: Importance Of Flood-water Inputs In the Water Balance Partitionsupporting
confidence: 82%